Pengaruh Harga Saham, EPS dan Market Value Terhadap Holding Period Saham Pada Saat Pandemic Covid-19 - Anis Rahayu; Tuti Zakiyah; Wahyuni Windasari (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2022)
This research was conducted with the aim to test the effect of stock prices, earnings per share and market value on the holding period of shares at the time of the covid-19 pandemic (on stocks listed in the Jakarta Islamic Index (JII) in 2020). The population in this study are all companies listed in the Jakarta Islamic Index (JII) in 2020. The sample collection technique in this study is using the purposive sampling method. In this study there were 22 samples of companies with a total of 190 trading days so that the total sample was 4,180. The analysis tool used is regression data panel using EViews 9. The results of this study showed that the stock price had a positive effect on the holding period of the stock, this is indicated by a prob value of 0.0000 < 0.05. Earnings per share positively affect the holding period of the stock, this is indicated by the value of the prob. of 0.0402 < 0.05. Market value negatively affects the holding period of the stock, this is indicated by the value of prob. of 0.0000 < 0.05. Variable stock price, earnings per share and market value together affect the holding period of the stock by 48%, while the rest is explained by variables outside the model Keywords: stock holding period, JII